2021
DOI: 10.4314/gmj.v55i3.4
|View full text |Cite
|
Sign up to set email alerts
|

Community acceptance, satisfaction, and support for case management of malaria of various degrees in selected rural communities in Ibadan, Oyo-State

Abstract: Objectives: This study aimed to assess communities’ perception and adoption of the evidenced-based malaria diagnosis and case management intervention targeted at under-five children. The effectiveness of trained Volunteer Community Health Workers (VCHWs) to diagnose malaria among under-five children using rapid diagnostic testing kit, provide treatment using Artemisinin Combination Therapy and rectal Artesunate were assessed.Design: A qualitative evaluation study was conducted in October 2015.Setting: Communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The results agree with our previous work on CO 2 + acetic acid corrosion. [8] 3.2 | BLC: Inhibition with 2-PI, 2-MBI, and 2-AETD Potentiodynamic polarization of carbon steel immersed in CO 2 saturated 1% (0.17 M) NaCl at 70°C with varying concentrations of 2-PI, 2-MBI, and 2-EATD are shown in Figures 4-6, respectively. Evidently, 2-PI is not effective in this application as it accelerates the overall cathodic kinetics and, hence, corrosion rate.…”
Section: Blc: Co 2 Saturated Brine Plus Acetic Acidmentioning
confidence: 99%
See 2 more Smart Citations
“…The results agree with our previous work on CO 2 + acetic acid corrosion. [8] 3.2 | BLC: Inhibition with 2-PI, 2-MBI, and 2-AETD Potentiodynamic polarization of carbon steel immersed in CO 2 saturated 1% (0.17 M) NaCl at 70°C with varying concentrations of 2-PI, 2-MBI, and 2-EATD are shown in Figures 4-6, respectively. Evidently, 2-PI is not effective in this application as it accelerates the overall cathodic kinetics and, hence, corrosion rate.…”
Section: Blc: Co 2 Saturated Brine Plus Acetic Acidmentioning
confidence: 99%
“…Pojtanabuntoeng et al found that corrosion mitigation was effective between pH 6.5 and 7, [7] while, in an earlier paper, we demonstrated that MDEA has useful, but limited, effectiveness for both TLC and BLC. [8] Organic corrosion inhibitors are commonly used to mitigate damage to carbon steel by restricting the kinetics of the cathodic reaction, or the anodic metal dissolution reaction, or both. As the review by Schmitt [9] shows, the efficiency of an organic inhibitor is generally related to its tendency to dynamically adsorb and desorb onto electrochemically active sites on metallic substrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation